Postwar Commercial Properties and Section 106: Piloting the Methodology for Evaluating Historic Significance (The National Academies Press, 2023)
NCHRP Web-Only Document 367: Postwar Commercial Properties and Section 106: Piloting the Methodology for Evaluating Historic Significance, from TRB's National Cooperative Highway Research Program, provides a guide for practitioners to better understand how to evaluate post-World War II commercial properties for National Register of Historic Places eligibility for transportation projects in compliance with Section 106 of the National Historic Preservation Act of 1966. The document is supplemental to NCHRP Research Report 1067: Postwar Commercial Properties and Section 106: A Methodology for Evaluating Historic Significances.

Guidebook for Implementing Intelligent Transportation Systems Elements to Improve Airport Traveler Access Information - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
TRB2019s Airport Cooperative Research Program (ACRP) Report 70: Guidebook for Implementing Intelligent Transportation Systems Elements to Improve Airport Traveler Access Information provides descriptions, component details, and examples of how airport ground access information can be disseminated using various intelligent transportation systems (ITS) technologies.The guidebook contains tables to help airport operators determine the applicability of certain ITS strategies based on airport operational needs and airport size.The printed version of the report includes an interactive CD-ROM designed to help explore and evaluate the information needs of various airport traveler market segments and to identify ITS technologies that best meet the needs of the airport user.The CD-ROM also contains a decision support tool that allows users to identify appropriate methods of delivering airport traveler information based on the airport traveler market segment.The CD-ROM is also available for download from TRB2019s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM Image Download the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively \

Runway Protection Zones (RPZs) Risk Assessment Tool Users’ Guide - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
TRB's Airport Cooperative Research Program (ACRP) Research Report 168: Runway Protection Zones (RPZs) Risk Assessment Tool Users2019 Guide helps airport operators evaluate the risk of an aircraft accident within an RPZ. Although runway protection zones (RPZs) are supposed to be clear of structures and people, it is still common for activities to occur within an RPZ for many reasons, and these reasons can be beyond the control of the airport operator.The report is accompanied by a tool used to assess the risk of an aircraft accident within the RPZ, and, based on that output, assess the risk to people and property, considering the population density and land use. The tool can be used to run scenarios for planning around an RPZ or if changes are being considered, for example a change in the threshold, extending a runway, removing a hazard, and planning for a new runway. Ideally, the Users2019Guide should be read before starting to use the tool.Chapter 4 has instructions for installing the tool, including how to download SQL, which is required to run the RPZ_RAT tool. For background on the development of the tool, see the Contractor2019s Final Report.Disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively \

Evaluation of Methodologies for Visual Impact Assessments - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2013)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 741: Evaluation of Methodologies for Visual Impact Assessments evaluates visual impact assessment (VIA) procedures, methods, and practices that satisfy or exceed National Environmental Policy Act (NEPA) and other requirements.The report documents VIA methodologies and approaches used in the United States and other countries, describes the decision making framework used to select specific VIA techniques for a given project, includes VIA best practice case studies from state departments of transportation, and highlights promising new developments in the field.

Building Information Modeling for Airports - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 70: Building Information Modeling for Airports summarizes current state of the art and practice for Building Information Modeling (BIM). BIM is a digital representation of a facility2019s physical and functional characteristics. BIM offers tools that allow airport decision makers to understand all components of a facility2014their location, and their attributes, both graphically and systematically2014to minimize the total cost of owning and operating an airport facility.The report provides a snapshot of experiences related to the emergence of BIM in North American airports. In addition to the report, a PowerPoint presentation details use-cases of BIM at airports.

Reducing Litter on Roadsides - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2009)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 394: Reducing Litter on Roadsides explores the state of the practice in reducing roadside litter as it involves state departments of transportation (DOTs). The report provides information concerning the prevention and removal of roadside litter, unfulfilled needs, knowledge gaps, and underperforming activities. It covers enforcement, education, awareness, and engineering methods for both litter prevention and collection.

Best Practices to Enhance the Transportation-Land Use Connection in the Rural United States - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2007)
TRB's National Cooperative Highway Research Program (NCHRP) Report 582: Best Practices to Enhance the Transportation-Land Use Connection in the Rural United States explores how to integrate land use and transportation in rural communities. The report also highlights programs and investment strategies designed to support community development and livability while providing adequate transportation capacity.

Microsurfacing - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 411: Microsurfacing explores highway microsurfacing project selection, design, contracting, equipment, construction, and performance measurement processes used by transportation agencies in the United States and Canada.Microsurfacing is a polymer-modified cold-mix surface treatment that has the potential to address a broad range of problems on today2019s highways.

Sustainable Pavement Maintenance Practices - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s National Cooperative Highway Research Program (NCHRP) Research Results Digest 365: Sustainable Pavement Maintenance Practices highlights the current practice in sustainable pavement maintenance and preservation.The report is designed to help quantify and understand how pavement maintenance and preservation practices minimize environmental impacts.As part of the development of this report, a general survey on sustainable pavement preservation and maintenance practices was issued to the state and provincial maintenance engineers in the United States and Canada. The full results of the survey and a summary of the survey are available for download as the following appendixes to NCHRP RRD 365.2022 Appendix A: Survey Results2022 Appendix B: Summary of Survey Results

Aesthetic Concrete Barrier Design - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2006)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 554: Aesthetic Concrete Barrier Design provides guidance for the aesthetic treatment of concrete safety shape barriers.

Implementing New Technologies in Maintenance Systems and Departments in Europe - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s Transit Cooperative Research Program (TCRP) Research Results Digest 71: Implementing New Technologies in Maintenance Systems and Departments in Europe summarizes the International Transit Studies Program mission of April 7-22, 2005, that investigated the application of new technologies in bus and rail transit operations in Germany, Austria, and France.

Going the Distance Together: A Citizen’s Guide to Context Sensitive Solutions for Better Transportation - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s National Cooperative Highway Research Program (NCHRP) Web-Only Document 184: Going the Distance Together: A Citizen2019s Guide to Context Sensitive Solutions for Better Transportation is designed to help people ask the right questions at the right time during the transportation planning process in order to help ensure that transportation projects fit the context of their community.Context sensitive solutions is a consensus-building process designed to allow citizens to become full collaborators in all aspects of transportation planning.Topics addressed in the report include transportation and the quality of life; the foundation of context sensitive solutions; shaping transportation decisions; understanding professional responsibility and design flexibility in project design; and partnerships through collaboration.The same project that developed NCHRP Web-Only Document 184 also produced a practitioner2019s guide to context sensitive solutions. That report will be published by the U.S. Federal Highway Administration. A link to that report will be available from this site once it is released.

Guide to Creating and Sustaining a Culture of Innovation for Departments of Transportation - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 885: Guide to Creating and Sustaining a Culture of Innovation for Departments of Transportation presents guidance for government transportation agencies on encouraging and sustaining a culture of innovation within the organization, its partners, and other stakeholders. A culture of innovation supports agency managers and staff efforts to encourage and accept innovation as a means to enhance the agency2019s success. This guide is designed to assist agencies in assessing their culture with respect to innovation, identifying ways to make the organization more adaptable and open to beneficial change, and sustaining the organization2019s adaptability to respond effectively to evolving technology, workforce, and public priorities.Accompanying this report is NCHRP Web-Only Document 248: Research on Creating and Sustaining a Culture of Innovation for Departments of Transportation documents the research process and provides key guidance to implement the research produced in NCHRP Research Report 885.

A Model for Identifying and Evaluating the Historic Significance of Post-World War II Housing - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 723: A Model for Identifying and Evaluating the Historic Significance of Post-World War II Housing provides an approach to the identification and evaluation of postwar housing resources that can be used within the framework of Section 106 of the National Historic Preservation Act and Section 4(f) of the Department of Transportation Act.The report includes a methodology for identification and evaluation of the National Register eligibility and non-eligibility of single-family housing built between 1946 and 1975. The report also includes a national context to understand the development of postwar housing and to help guide the evaluation of postwar residential types.TR News 292: May-June 2014 includes an article about the report.

Practices for Unbound Aggregate Pavement Layers - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2013)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 445: Practices for Unbound Aggregate Pavement Layers consolidates information on the state-of-the-art and state-of-the-practice of designing and constructing unbound aggregate pavement layers. The report summarizes effective practices related to material selection, design, and construction of unbound aggregate layers to potentially improve pavement performance and longevity.

U.S. and International Approaches to Performance Measurement for Transportation Systems - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2008)
TRB Conference Proceedings 44: U.S. and International Approaches to Performance Measurement for Transportation Systems is the proceedings of a September 2007 conference that explored opportunities for and experiences in using performance measurement as a strategic tool to better communicate goals, objectives, and results to a wide range of stakeholder groups.

Smart Growth and Transportation: Issues and Lessons Learned - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s Conference Proceedings 32: Smart Growth and Transportation: Issues and Lessons Learned summarizes the highlights of a conference2014Providing a Transportation System to Support Smart Growth: Issues, Practice, and Implementation2014held September 8-10, 2002, in Baltimore, Maryland. The conference was designed to address how transportation policy makers and frontline professionals can support the diverse goals that different communities associate with smart growth.

Coordinated Approaches to Expanding Access to Public Transportation - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2007)
TRB2019s Transit Cooperative Research Program (TCRP) RRD 81: Coordinated Approaches to Expanding Access to Public Transportation explores a study mission that examined coordinated approaches to expanding access to public transportation in the United Kingdom, the Netherlands, Sweden, and France.

Chip Seal Best Practices - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 342: Chip Seal Best Practices examines ways to assist in the development and implementation of pavement preservation programs by identifying the benefits of using chip seal as part of a preventive maintenance program and by highlighting advanced chip seal programs in use around the world. The report includes approximately 40 best practices in the areas of chip seal design methods, contract administration, equipment practices, construction practices, and performance measures. According to the report, the increased use of chip seals for maintenance can be a successful, cost-effective way of using preventive maintenance to preserve both low-volume and higher-volume pavements.

A Multivariate Analysis of Crash and Naturalistic Driving Data in Relation to Highway Factors - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2013)
TRB2019s second Strategic Highway Research Program (SHRP 2) Report S2-S01C-RW-1: A Multivariate Analysis of Crash and Naturalistic Driving Data in Relation to Highway Factors explores analysis methods capable of associating crash risk with quantitative metrics (crash surrogates) available from naturalistic driving data.Errata: The foreword originally contained incorrect information about the project. The text has been corrected in the online version of the report. (August 2013)